The Emperor's New Clothes: When Nothing is Everything - Proni, Giampaolo (ZoneModa Journal, 2022)
The Emperor's New Clothes (Danish: “Kejserens nye klæder”, 1837) is one of the most famous Andersen’s fairy tales. It’s a typical apologue, with the vice of vanity as its target. The text will be subjected to a first reading to evince the narrative strategy and moral themes. A further, semiotic analysis of the text will be conducted on the basis of the first reading, so to expose the coding implied in the narration. Those codes will show the connection between dressing behaviour and the general system framing a human society. A narrative text, as Andersen’s tale, encodes the author’s implementation and re-writing of the social system, its map of values, both normative (moral) and phenomenological (experiential), and the reciprocal interaction. In particular, the semiotic analysis of The Emperor's New Clothes allows us to extract a representation of dressing behaviour and highlight its structure and dynamics.